A novel method of recognizing liquefied honey. (15th April 2018) - Płowaś-Korus, Iwona; Masewicz, Łukasz; Szwengiel, Artur; Rachocki, Adam; Baranowska, Hanna Maria; Medycki, Wojciech
Highlights: A simple method of recognizing liquefied honey is proposed. The method relies on the water influence on carbohydrates content and pH. Temperature of 30 °C results in permanent changes in a honey molecular structure. Abstract: The content of glucose, fructose, sucrose, maltose and water were determined for multiflorous honey of Great Poland. The measurements were carried out for different fractions of honey and also for the liquefied honey at 40 °C. Water activity and pH were both determined for all samples. A new method of recognizing liquefied honey is proposed based on the water influence on pH and the monosaccharides and disaccharides contents. The simple function of quadratic polynomial enabled to reveal the different character of the liquefied honey. The electrical conductivity behavior of different dry matter samples of honey are presented in the wide range of temperature. The proton spin–lattice relaxation measurements were recorded for the crystalline fraction in the magnetic field range covering the proton Larmor frequencies from 0.01 to 25 MHz and in the wide range of temperature. Heating the honey at 30 °C results in the irreversible molecular structure changes.